Glucose Deprivation Induced by Acarbose and Oncolytic Newcastle Disease Virus Promote Metabolic Oxidative Stress and Cell Death in a Breast Cancer Model - Obaid, Qayssar A.; Al-Shammari, Ahmed Majeed; Khudair, Khalisa K. (Frontiers in Molecular Biosciences, 2022)
Cancer cells are distinguished by enhanced glucose uptake and an aerobic glycolysis pathway in which its products support metabolic demands for cancer cell growth and proliferation. Inhibition of aerobic glycolysis is a smart therapeutic approach to target the progression of the cancer cell. We employed acarbose (ACA), a particular alpha-glucosidase inhibitor, to induce glucose deprivation combined with oncolytic Newcastle disease virus (NDV) to enhance antitumor activity. In this work, we used a mouse model of breast cancer with mammary adenocarcinoma tumor cells (AN3) that were treated with ACA, NDV, and a combination of both. The study included antitumor efficacy, relative body weight, glucose level, hexokinase (HK-1) level by ELISA, glycolysis product (pyruvate), Total ATP, oxidative stress (ROS and reduced glutathione), and apoptosis by immunohistochemistry. The results showed significant antitumor efficacy against breast cancer after treatment with combination therapy. Antitumor efficacy was accompanied by a reduction in body weight and glucose level, HK-1 downregulation, inhibition of glycolysis products (pyruvate), Total ATP, induction of oxidative stress (increase ROS and decrease reduced glutathione), and apoptotic cell death. The findings propose a novel anti-breast cancer combination involving the suppression of glycolysis, glucose deprivation, oxidative stress, and apoptosis which can be translated clinically.